Hydroxychloroquine improves pregnancy outcomes of women with positive antinuclear antibody spectrum test results - Ye, Shenglong; Liu, Yuanying; Zhao, Xueqing; Ma, Yue; Wang, Yongqing (Frontiers in Medicine, 2023)
Background: Empirical use of Hydroxychloroquine (HCQ) in patients with positive antinuclear antibody spectrum (ANAs) test result is controversial regarding its impact on improving perinatal outcomes. This study aimed to investigate the effect of HCQ on adverse pregnancy outcomes associated with placental dysfunction in ANAs-positive patients. Methods: The study included pregnant women with positive ANAs test result from 2016 to 2020 in our center, and divided into a weakly positive and a positive group in just ANA positive patients among them. Univariate and multivariate analyses were conducted to determine the effect of HCQ on pregnancy outcomes in each subgroup. Stratified and interactive analyses were performed to assess the value of HCQ in improving pregnancy outcomes. Results: (i) A total of 261 cases were included, accounting for 30.60% of pregnancy complicated with autoimmune abnormalities, and 65.12% of them used HCQ during pregnancy. (ii) The application of HCQ significantly reduced the incidence of early-onset preeclampsia (1.18% vs. 12.09%, p = 0.040) and small-for-gestational-age infants (10.06% vs. 25.84%, p = 0.003) in the ANAs-positive population, increased birth weight (3075.87 ± 603.91 g vs. 2847.53 ± 773.73 g, p = 0.025), and prolonged gestation (38.43 ± 2.31 vs. 36.34 ± 5.45 weeks, p < 0.001). (iii) A total of 185 just ANA-positive patients were stratified according to titers. Among them, the rate of HCQ usage was significantly higher than that in the weakly positive group (81.03% vs. 58.27%, p = 0.003). (vi) Stratified univariate analysis showed that HCQ usage in the ANA-positive group could reduce the incidence of preeclampsia (2.13% vs. 27.27%, p = 0.019) and prolong gestation (38.29 ± 2.54 vs. 34.48 ± 7.68 weeks, p = 0.006). In the ANA-weakly positive group, HCQ significantly reduced the incidence of preeclampsia (6.76% vs. 28.30%, p = 0.002), early-onset preeclampsia (1.35% vs. 13.21%, p = 0.027), and small-for-gestational-age infants (7.89% vs. 35.19%, p < 0.001). Multivariate regression analysis showed that HCQ significantly reduced the incidence of preeclampsia in both groups. Intergroup interaction analysis showed no significant difference in the value of HCQ in reducing the incidence of preeclampsia between the two groups. Conclusion: ANAs positivity is an important abnormal autoimmunity type in pregnancy. HCQ can be considered as a choice for improving adverse pregnancy outcomes related to placental dysfunction, such as preeclampsia, in this population.